Peningkatan Keterampilan Menulis Puisi Melalui Penggunaan Media Gambar dan Glosarium Diksi Peserta Didik SMPN 6 Bontang - Kartini, Kartini (Jurnal Didaktika Pendidikan Dasar, 2021)
The problem in this research is the low poetry writing skills of the VIII grade student sof State Junior High School 6 Bontang. This type of research is classroom action research. Retrieval of data using observation, tests, and interviews. The author conducted two treatments in this study. The first without using media and the second using image media and dictionaries glossary. Based on the results of the study, it can be stated that learning using image media and dictionaries can increase the activeness and skills of writing poetry for VIII grade students. The skill of writing poetry in students has increased, we can see from the average score of the students. In the initial conditions the average value is 40, in the first cycle it increases to an average of 60, (still not reaching the KKM value) in the second cycle it has increased quite significantly to an average value of 85. Thus it can be said that the application of image media and dictionaries glossary is quite significant in improving the poetry writing skills of grade VIII students of SMP Negeri 6 Bontang.